Facilitative recovery of cyclodextrin glucanotransferase using chromatographic strategies - Sivapragasam, Magaret (2014)
Cyclodextrin glucanotransferase (CGTase), are monomeric enzymes that are secreted extracellularly which catalyzes transglycosylation reactions via its glucosyl residues and are used as an acceptor in forming cyclodextrins (CD). CD’s, are widely used in the pharmaceutical, medicine, food, textile, agriculture and the cosmetic industries. Purifying CGTase is often a complicated task due to its heterogeneity, complexity and instability. To harness, it requires a set of downstream processing which typically consist of a cascade of recovery steps. The CGTase used in this study originated from Bacillus sp G1, which was successfully cloned and expressed in E.coli BL21. Recombinant CGTase was found to be growth related with maximum enzyme production at 167 U/mL after 10 hours of culture at 37⁰C in an orbital shaker with constant speed of 175 rpm. A series of pre purification strategies were carried out to determine the best method to concentrate the enzyme for subsequent purification procedures. Ammonium sulphate precipitation (70% saturation point) and dialysis tubing (SnakeSkin and flat tubing-with MWCO 3.5k) were investigated for concentrating the CGTase from E.coli culture. Results showed dialysis using SnakeSkin method to be superior to ammonium sulphate precipitation with CGTase yield of 148 U/mL and 19 U/mL respectively. Adsorbents used were mixed mode (of hydrophobic and ion exchange) ion exchangers, and immobilised metal affinity chelating. These adsorbents packed in a Tricorn 10/50 column, were screened for their suitability to purify CGTase by buffer optimization, frontal analysis and static binding evaluations. Purification yields using mixed mode chromatography were observed by using the mixed mode resin, PPA HyperCel which obtained 97% of CGTase enzyme recovery. Recovery performance were compared with other chromatography methods which is the ion exchange chromatography at 78% recovery and immobilised metal affinity chromatography at 87% recovery.